Structure formation in pin-like joining using vibration welding technology - Wolf, Michael; Drummer, Dietmar (Journal of Advanced Joining Processes, 2023)
Joining technologies have a decisive role in the product development cycle. Welding processes are widely used industrially, which, in addition to a number of advantages, also have limitations on possible material combinations. Therefore, novel joining processes are necessary, like the joining using pin-like structures using the vibration welding technology. Beside known material and process correlations, the structure formation effect the resulting bond properties. For this reason, the structuring step was analyzed within this study. The investigations allowed a model-based description of the formation of the pin-like structures to be derived. In addition, the investigations show that an additional energy input during pin development prevents a pin defect during tool pull removement due to a reduced weld line. This can have particular advantages for material combinations with a bonding-partner of high stiffness.<br
Keywords: Joining; Multi-material; Pin-like structures; Adhesion-incompatible